REVITALISASI NILAI-NILAI PANCASILA SEBAGAI PENDIDIKAN KARAKTER - Chairiyah chairiyah (Universitas Sarjanawiyata Tamansiswa, 2014)
Â Abstract: Pancasila as the Indonesian state should be the guideline for all Indonesian citizens in various spheres of life. But in fact this time the noble values of pancasila increasingly eroded due to the influence of westernization and globalization are less well filtered. Indication of the waning practice of pancasila values can be seen from the increasing number of cases involving young people which reflects the weak character of the nation, such as the rise of student brawls, clashes between students, anarchist demonstrations, cases immoral, crime, and so forth. To restore the values of pancasila in the life of society, nation and state need for revitalization efforts. Revitalization means process, ways, and actions to revive something that was previously lacking empowered. Through revitalization, expected values of pancasila became more terberdaya in Indonesian society. All parties can actively participate in efforts to revitalize pancasila values in all aspects of life. One of them is to instill the values of pancasila through teaching in schools in an effort to form a good character of the younger generation. The younger generation as a potential successor to the leadership of the Indonesian nation must maintain and practice the values of pancasila to people's lives and the country in the future for the better in the sense of the Indonesian nation has identity as a nation of character .Â